Próby z Kundery. Kilka uwag na temat figuratywności - Skibska, Anna Maria (Slavia Occidentalis, 2014)
The essay tends to illuminate a series of rhetorical operations, presented and commented in the literary works of Milan Kundera, in order to discuss their performative activity, conjoined with their important participation in the textual structure. According to the author of L’art du roman, a figure of metaphor seems to be at the forefront in the privileged realm of novel, however, its phenomenological character demands to be put in question since the aforementioned figure confronts an ironic necessity regarding the apophantic essence of writing. Thus the negative work of irony manages to destabilize the phenomenological or existential metaphor that is consequently perceived in the opposition to the ornament metaphor, which is to determine the poetic imagination. Furthermore, Kundera’s irony also results in a significant involvement of the set of subsequent rhetorical devices, and among of them an extra-ordinary event of ellipsis should be taken into consideration for it perfectly renders the idyllic desire of (a) non-presence, manifested or illustrated by the case of Agnes in Immortality. Kundera’s texts, reread in the intertextual perspective, partly indicated by the writer himself, partly revealed as the essay’s intention, establish therefore an unlimited possibility of interpretation, possibility that has to remain a sequence of attempts, streaked with the art of misreading.